A new species of Phyllium (Phyllium) Illiger, 1798 from Mindanao, Philippines (Phasmida, Phylliidae) - Cumming, Royce T. (Zootaxa, 2017)
A new species of leaf insect, Phyllium (Phyllium) fallorum n. sp. is described and illustrated. In addition a key to the current known species of Phyllium Illiger, 1798 from the Philippines is provided. This species is currently only known from the single unique holotype, which will be deposited in the San Diego Natural History Museum. Measurements of anatomical figures were made to the nearest 0.1 mm. Photos were taken using a Canon 5D Mark II and a MP-E 65mm macro lens and stacked using Zerene photo stacking software, version 1.04, 64-bit. Currently, ten species of Phyllium Illiger, 1798 have been described from the Philippines, with Phyllium (Phyllium) fallorum n. sp. the eleventh. Of the eleven known species from the Philippines, five are only known from female specimens.